The expression of chemokines CCL19, CCL21 and their receptor CCR7 in oral squamous cell carcinoma and its relevance to cervical lymph node metastasis - Oliveira-Neto, Helenisa Helena; Souza, Pedro Paulo Chaves de [UNESP]; Da Silva, Márcio Roberto Barbosa; Mendonça, Elismauro Francisco; Silva, Tarcília Aparecida; Batista, Aline Carvalho (Springer Nature, 2013)
The purpose of this study is to determine the expression of CCL19, CCL21, and CCR7 in samples of oral squamous cell carcinoma (OSCC) and their relationship with clinical and microscopic parameters. A comparative analysis was made of the mRNA expression of these chemokines and receptor in OSCC and normal oral mucosa. The immunoexpression of CCR7, CCL19, and CCL21 was also verified in OSCC and lymph nodes. Statistical significance was accepted at P < 0.05. Similar levels of CCR7, CCL19, and CCL21 mRNA in OSCC and normal oral mucosa were seen. A low expression of CCL19 and CCL21 in the intra- and peritumoral regions was observed. Scarce CCL19+ and CCL21+ cells were also noted in metastatic and non-metastatic lymph nodes. No association was found between the expression of these chemokines and clinical and microscopic parameters. Our findings would suggest that CCL19 and CCL21 may not be associated with cervical lymph node metastasis or other clinical and microscopic factors in OSCC. © 2012 International Society of Oncology and BioMarkers (ISOBM).
Keywords: CCL19; CCL21; CCR7; Chemokine; Lymph node; Metastasis; Oral squamous cell carcinoma; chemokine; chemokine receptor; chemokine receptor CCR7; macrophage inflammatory protein 3beta; messenger RNA; monocyte chemotactic protein 5; adult; aged; cell count; cell proliferation; cervical lymph node; clinical article; clinical feature; comparative study; controlled study; disease association; female; human; human cell; human tissue; lymph node metastasis; male; metastasis potential; mouth mucosa; mouth squamous cell carcinoma; nucleotide sequence; oncological parameters; priority journal; protein expression; protein function; tumor localization; Carcinoma, Squamous Cell; Chemokine CCL19; Chemokine CCL21; Female; Humans; Lymph Nodes; Lymphatic Metastasis; Male; Middle Aged; Mouth Neoplasms; Receptors, CCR7; RNA, Messenger; Treatment Outcome